Facile preparation, characterization and application of novel sugarcane bagasse-derived nanoceria-biochar for defluoridation of drinking water: kinetics, thermodynamics, reusability and mechanism - Verma V.; Sharma Y.C. (My University, 2025)
Although expensive, rare-earth oxides are well known for being powerful defluoridation agents. Being costlier, cerium is used as a hybrid adsorbent in conjunction with a prudent and environmentally benign substance like biochar. The novel CeO2/BC (surface area 260.05 m2/g) composite was shaped using the facile chemical precipitation technique without any cross-linkers. Surface properties of synthesised CeO2/BC were investigated using powder XRD, FTIR, BET, pH point of zero charge and SEM. According to XRD analysis, immobilized Ce is primarily in form of CeO2, while pristine biochar is in an amorphous state. Batch mode adsorption tests were carried out with different solution pH, F- initial concentration, adsorbent dosage and contact time and counter anions. CeO2/BC can be used in a varied pH range (2-10) but shows maximum removal at pH 4. The Langmuir adsorption isotherm and a pseudo-second-order kinetic model are best fitted to support the adsorption process with a maximum Langmuir adsorption capacity of 16.14 mg/g (F- concentration 5 to 40 mg/L). The removal phenomenon is non-spontaneous in nature. The plausible mechanism of fluoride uptake was explained using XPS and pHPZC, and it was demonstrated that the fluoride was mainly removed by ion exchange and electrostatic attraction. The adsorbent could be successfully used up to fourth cycle after regenerating. © 2023. The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.